Advantage in diversity: school paths and future orientations of mixed origin 9th graders in Portugal - Mateus, S. (18th Nordic Migration Conference, 2016)
The descendants of immigrants have been portrayed internationally as actors in particularly intense cumulative transition experiences: transition between cultural frames and geographical spaces, between levels of education, or to adulthood. They are sociologically analyzed through the lens of disadvantage and vulnerability, but also the advantage, for its adaptation and innovation competences, and the ability to question and build complex affiliations. Our presentation focuses on a specific segment of descendants of immigrants: those with mixed origin, with a foreign parent and one native parent, actors par excellence of the fluid, plural and complex identities of contemporaneity. It is a less visible group in both American and European sociological production. However, the group reveals distinctive singularities. The analysis will focus on their social profiles, conditions, objective and subjective trajectories, and future orientations. The discussion is based on data from a mixed-method research, finished in 2013 - ITEOP (Survey of Educational Pathways and Vocational Orientations), involving 1,194 9th-grade students (aged 14-19), surveyed at 13 schools in the Lisbon, Setubal and Faro regions, in Portugal. The surveyed students include 789 natives and 405 children of immigrants; within these 95 are mixed origin Portuguese/other origin. The comparative analysis shows heterogeneity of characteristics, paths and experiences within the group of descendants of immigrants; and confirms that the mixed origin students are closer to native students in their paths. They meet or experience more favorable conditions than other descendants. They carry hybrid identities and bicultural skills that creatively mix cultural elements, triggering more ambitious, structured and coherent future orientations. The patterns identified in these students show more positive school integration and success, privileged interaction frameworks and strong individual agency.